Weighing excited nuclear states with a Penning trap mass spectrometer - Weber, Christine; Kluge, Heinz-Jürgen (Physics letters, 2005)
We report on high-accuracy mass measurements and isomer identification of 187Pb. In this nuclide, two close-lying isomeric states are known from α-decay studies. With the combined use of the ISOLDE resonance ionization laser ion source and the Penning trap mass spectrometer ISOLTRAP the energy difference of 187Pb and 187mPb was determined to be E=33(13) keV. This is the lowest isomeric excitation energy ever determined by weighing nuclei.